2020
DOI: 10.1111/jfpp.15001
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ultrasound treatment on the efficiency of membrane clarification of carrot juice

Abstract: Large particles in carrot juice create a turbid appearance; therefore, membrane treatment can be used to clarify it. To evaluate the effect of ultrasound on the membrane processing efficiency, ultrasound (1,000 W, 20 kHz) was applied to carrot juice and membrane unit. Results showed that this process can increase the permeate flux by about 10–3 kg/m2s, and the rate of the increased flux caused by the ultrasound increases with increasing transmembrane pressure and feed flow rate; as, the best performance was ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 37 publications
0
2
0
Order By: Relevance
“…Ultrasound is an unconventional physical approach for fouling mitigation during membrane separation. The ultrasonic modification has been observed to lessen cake layer accretion, increase permeates flux, and enhance juice cloud stability during MF clarification of pomegranate juice [ 81 ] as well as carrot juice [ 42 , 82 ]. Aghdam et al [ 81 ] stated that ultrasound treatment lowered the overall fouling resistance in pomegranate juice clarification using MF, with cake resistance and irreversible fouling resistance.…”
Section: Strategies For Curtailing Membrane Fouling To Enhance the Fr...mentioning
confidence: 99%
See 1 more Smart Citation
“…Ultrasound is an unconventional physical approach for fouling mitigation during membrane separation. The ultrasonic modification has been observed to lessen cake layer accretion, increase permeates flux, and enhance juice cloud stability during MF clarification of pomegranate juice [ 81 ] as well as carrot juice [ 42 , 82 ]. Aghdam et al [ 81 ] stated that ultrasound treatment lowered the overall fouling resistance in pomegranate juice clarification using MF, with cake resistance and irreversible fouling resistance.…”
Section: Strategies For Curtailing Membrane Fouling To Enhance the Fr...mentioning
confidence: 99%
“…Aghdam et al [ 81 ] stated that ultrasound treatment lowered the overall fouling resistance in pomegranate juice clarification using MF, with cake resistance and irreversible fouling resistance. Similarly, Hemmati et al [ 42 ] investigated the influence of ultrasound at (1000 W, 20 kHz) on the permeation flux and during MF membrane filtration of Carrot Juice. The author observed that the permeate flux was increased by almost 10 −3 Kg/m 2 s at a TMP of 1 bar and a flow rate of 15 m/s.…”
Section: Strategies For Curtailing Membrane Fouling To Enhance the Fr...mentioning
confidence: 99%